QUALITY BY DESIGN APPROACH FOR DEVELOPMENT AND OPTIMIZATION OF NITRENDIPINE LOADED NIOSOMAL GEL FOR ACCENTUATED TRANSDERMAL DELIVERY - SHARMA, ABHISHEK; HARIKUMAR, S. L. (International Journal of Applied Pharmaceutics, 2020)
Objective: The purpose of the present investigation was to develop and optimize nitrendipine loaded niosomal gel for transdermal delivery using quality by design approach. Methods: Niosomal formulations were developed by application of the thin-film hydration method using different ratios of span 60, cholesterol, temperature, and optimized by three factors-three levels Box-Behnken statistical design. The independent variables were non-ionic surfactant, cholesterol, and temperature, while vesicle size, polydispersity index, and entrapment efficiency were dependent variables. The nitrendipine loaded optimized formulation was incorporated into gel and evaluated for in vitro release, ex-vivo skin permeation, confocal laser scanning microscopy, and histopathological studies. Results: The optimized formulation showed the vesicular size of 226.1±4.36 nm, polydispersity index of 0.282±0.012, and entrapment efficiency of 95.34±3.18% with spherical morphology. The optimized niosomal gel formulation showed transdermal flux 127.60 µg/cm2h through albino Wistar rat skin. Niosomal gel was proved significantly superior by confocal laser scanning microscopy for satisfactory permeation and distribution of gel, deep into the rat skin. Furthermore, dermal safety was confirmed by histopathological studies for transdermal application. Conclusion: It was concluded that the developed niosomal gel overcomes the limitation of low penetration through rat skin and could be a potential nano vesicular system for transdermal delivery.